Analysis of the economic behavior of the university students of the city of Medellín [Análisis del comportamiento económico de los estudiantes universitarios de la ciudad de Medellín] (2017)
Economic psychology studies issues related to the economic decision-making of individuals. In this sense it is relevant to study the behavior regarding savings, expenditure and financial planning of different groups to understand their economic-financial behavior. This article analyzes the way in which cash is administered by students of a private university in the city of Medellín, considering aspects related to savings, spending and financial planning tools, such as budgeting. © 2017.